Contagion and downside risk in the REIT market during the subprime mortgage crisis - Chen, Ming-Chi; Tsai, Hsiu-Jung; Sing, Tien-Foo; Yang, Chih-Yuan (International Journal of Strategic Property Management, 2015)
This study empirically tests the contagion effects in stock and real estate investment trust (REIT) markets during the subprime mortgage crisis by using daily stock- and REIT-markets data from the following countries and international bodies: the United States, the European Union, Japan, Hong Kong, Singapore, Australia, and the global REIT market. We found a significant and positive dynamic conditional correlation (DCC) coefficient between stock returns and REIT returns. The results revealed that the REIT markets responded early to market shocks and that the variances were higher in the post-crisis period than in the pre-crisis period. Evidence supporting the contagion effects includes increases in the means of the DCC coefficients during the post-crisis period. The Japanese and Australian REIT markets possess the lowest time-varying downside systematic risks. We also demonstrated that the “DCC E-beta” captures more significant downside linkages between market portfolios and expected REIT returns than does the standard CAPM beta.First Publish Online: 1 Apr 2015